2011
DOI: 10.3390/insects2040475
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Resistance of Six Hawaii-Grown Bamboo Species to Attack by the Subterranean Termites Coptotermes formosanus Shiraki and Coptotermes gestroi (Wasmann) (Blattodea: Rhinotermitidae)

Abstract: Bamboo is widely grown and utilized as a construction material around the world, particularly in the tropics. At present, there are about 70 bamboo species and varieties recorded from Hawaii. The objective of our study was to determine the relative resistance of six Hawaii-grown bamboo species to attack by Coptotermes formosanus Shiraki and Coptotermes gestroi (Wasmann). Four-week laboratory feeding trials were performed as described in standard E1-09 of the American Wood Protection Association (AWPA 2009). Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This result can be explained by the followings: b The high proportion of Silica contained into the treated palm wood influence termite damage and plays a significant role in its termite resistance (Dhawan et al, 2007). b High ash content reduces the food value of wood for termites because it is not absorbed in the gut body and passes through (Hapukotuwa and Grace, 2011). b Some minerals in wood can have a toxic effect on the pests or disturb their physiology (Doi et al, 1998;Kneip et al, 2007).…”
Section: Mineral Composition Of Salt-treated Palm Wood and Its Influementioning
confidence: 99%
“…This result can be explained by the followings: b The high proportion of Silica contained into the treated palm wood influence termite damage and plays a significant role in its termite resistance (Dhawan et al, 2007). b High ash content reduces the food value of wood for termites because it is not absorbed in the gut body and passes through (Hapukotuwa and Grace, 2011). b Some minerals in wood can have a toxic effect on the pests or disturb their physiology (Doi et al, 1998;Kneip et al, 2007).…”
Section: Mineral Composition Of Salt-treated Palm Wood and Its Influementioning
confidence: 99%
“…Although both species exhibited similar feeding preferences for different types of lumber (Hapukotuwa and Grace 2011a) and bamboo (Hapukotuwa and Grace 2011b), C. gestroi was found to have a slower feeding rate than C. formosanus (Uchima and Grace 2003b). Coptotermes gestroi also suffers greater mortality than C. formosanus under desiccating conditions (Shelton and Grace 2003).…”
Section: Biological and Behavioral Differencesmentioning
confidence: 99%
“…Bamboo is also widely grown and used as a construction material around the world (Hapukotuwa and Grace 2011). Bamboo, like cocowood, belongs to the grass family.…”
Section: Introductionmentioning
confidence: 99%
“…No previous work has evaluated the natural resistance of cocowood to termite attack in field trials. However the natural resistance of a variety of bamboo species to feeding by subterranean termites has been evaluated in laboratory and field trials (Hapukotuwa and Grace 2011;Lifang et al 2010;Okahisa et al 2006;Mishra and Rana 1992). In contrast to true wood it was found that overall the natural durability of bamboo is not closely related to density, with many specimens lasting less than 2 years in a field exposure (Lifang et al 2010).…”
Section: Introductionmentioning
confidence: 99%